Extranjeros en el museo : una reflexión sobre la recepción de la obra de arte - Belgrano, Mateo (Sapientia, 2019)
It is a common place to think of aesthetic reception as hospitality. The work of art is a foreigner, as it brings a strange novelty to our daily lives, which knocks on our door and we should (should we?) host it. Are we guests or foreigners in the museum? Do we behave in the aesthetic experience as guests? For George Steiner, the work is a “presence” of the other and the aesthetic experience must be understood as a encounter of freedoms. If aesthetic reception is an encounter, this will entail an ethic of reception. The work is a free donation that prostrates before the freedom of the spectator, before the acceptance or rejection and that is why it is essential to be hospitable with it. Unlike Steiner, I argue that the aesthetic experience does not have to do with accepting another perspective or another freedom, but it has to do with being open to the experience of feeling foreign, of feeling other. In other words, the experience of another, the work of art, reshaping the world that is familiar and comfortable to me.